KEEFEKTIFAN MODEL SOMATIC, AUDITORY, VISUALIZATION, INTELLECTUALLY (SAVI) TERHADAP HASIL BELAJAR SBDP KARYA ORIGAMI KELAS III SD GUGUS RUJAKBELING KECAMATAN KEBUMEN. - Irma Kumala Sari; Rokhmaniyah Rokhmaniyah; Tri Saptuti Susiani (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
The Somatic Auditory Visualization Intellectually (SAVI) model is one of innovative learning models. It needs to accomplish learning purposes. The study aimed to examine the effectiveness of SAVI model on third grade origami project learning outcomes. The research was a quasi-experimental research in the form of Nonequivalent Control Group Design. The population was all third grade students of elementary schools in Rujakbeling cluster, Kebumen sub-district in academic year of 2019/2020. The sampling technique used cluster random sampling. Data collection techniques included t-test, n-gain test and effect size test. The result showed the value between the experimental class and the control class.  The t-test was 0.000<0.05, N-Gain was 0.4550>0.2747, and effect size was 2.123>1.291. It concludes that the Somatic Auditory Visualization Intellectually (SAVI) model is more effective in improving third grade origami project learning outcomes of elementary schools in Rujakbeling cluster, Kebumen sub-district.